EFFECTS OF STRENGTH TRAINING WITH BLOOD FLOW RESTRICTION AND ELECTROSTIMULATION ON MUSCLE STRENGTH AND ACTIVITY – STUDY PROTOCOL - da Silva, Maria Vitória Gonçalves [UNESP]; Soares, Isabela Cristina [UNESP]; de Lima, Leonardo Coelho Rabello [UNESP]; Pedroni, Cristiane Rodrigues [UNESP] (Elsevier, 2024)
Background Increasing muscle strength may allow an athlete to improve their performance while reducing the risk of injury. Blood Flow Restriction (BFR) has emerged as an alternative for increasing muscle strengh because it can promote physiological changes and hypertrophy with a lower degree of mechanical overload. When combined with Neuromuscular Electrostimulation (NME) it offers the possibility of hypertrophy with greater activation of motor units, potentially increasing the effects of BFR. Objectives To evaluate the effects of strength training with BFR combined with NME of the quadriceps muscle in physically active individuals on parameters of strength and muscle activation. Methods This protocol is a randomized clinical trial with a blinded evaluator for groups and statistical analysis. Eligibility criteria will be age between 18 and 35 years old; both sexes and physically active according to the International Physical Activity Questionnaire. The following criteria are not considered appropriate: Body Mass Index over 30; use of stimulants in the 24 hours before the examinations; risk factors for thromboembolism and hypertension. Anthropometric data will be collected, followed by blood pressure measurement and kirtometers. Subjects will be randomly divided into three groups: Blood Flow Restriction Group (BFRG), Blood Flow Restriction and Electrostimulation Group (BFREG) and Conventional Exercise Group (CEG). A Vascular Doppler will be used to measure Total Occlusion Pressure (TOP). Maximum Repetition Test (1RM) unilateral will be used to determine the load during exercise, with adjustment in four weeks. An isokinetic dynamometer in concentric/eccentric mode at two angular speeds will be uses to assess muscle strenght: 60º/s and 180º/s, and isometric strength by the 30s test at 30º and 60º. Surface Electromyography (EMG) will be used to record the electrical activity of the quadriceps muscles. The intervention protocol consists of four sets of 30, 15, 15, 15 repetitions in the chair for extension, with one minute rest between sets, a load of 30% 1RM and 50% of POT, with adjustment of 5% each week up 80% of POT. The BFREG follows the same methodology, with an asymmetric biphasic current, frequency of 50Hz and a pulse duration of 400us. In the CEG the exercise will be performed without intervention in three sets of ten repetitions at 70% of 1RM. The training lasts eight weeks and takes place twice a week, with re-evaluation at the end of the training. The distribution of normality will be analysed by the Shapiro-Wilk test. To analyse the effect of group and the interventions, ANOVA for repeated measures and Bonferroni post test will be performed. The significant level adopted will be 5%. Conclusion It is reasonable to assume that BFR and the intervention associated with electrostimulation are superior to conventional training in terms of strength and muscle recruitment parameters. Implications Because BFR requires a reduced load and it has been hypothesised that its effects are similar to those of conventional training, BRF offers mechanical and physiological benefits. Reduced loading may produce the same results in terms of hypertrophy and increased muscle strength in individuals without joint overload and prolonged loading.